IMF Survey, Volume 33, Issue 13. (IMF Survey; IMF Survey, 2004)
After serving for three years as the first director of the IMF's Independent Evaluation Office (IEO), Montek Singh Ahluwalia, an Indian national, left the IEO to take up a cabinet-level position as Deputy Chair of India's Planning Commission, which is chaired by the Prime Minister. Christine Ebrahim-zadeh of the IMF Survey spoke with him about his experience at the IEO.